Reviews of Science for Science Librarians: Low-FODMAP Diets for Irritable Bowel Syndrome and Related Disorders. Issue 3 (3rd July 2019) - Stankus, Tony
ABSTRACT: While there are a number of prescription medical treatment options for the tens of millions of Irritable Bowel Syndrome sufferers in the US, their effectiveness in symptom control varies significantly among individuals. Without necessarily discontinuing contemporary prescription medications or giving up hope for improved performance in new ones being trialed, most IBS patients today are on some form of prescribed or self-adopted restrictive diet as part of their symptom management. This paper will review the literature of some of those diets, particularly one called the low-FODMAP diet, used alongside, or instead of other treatments.